Produção e qualidade de forragens e atributos de um Argissolo vermelho - Pizzani, Rodrigo (2008)
In Brazil, most soils used in the livestock presents some fertility limitations. One of the alternatives to improve the soils quality is the introduction of perennial species, including grassy and associated legumes and correction of the soil that it will hold the cultures forage crop. There s a lack of Information and researches on soil quality improvement using perennial forages. Therefore, the objective of this work was to evaluate different systems of forage cultures constituted by Pennisetum americanum, Arachis pintoi and Stylosanthes guianensis associated with Cynodon dactylon and both isolated species, with and without mineral fertilizer, and evaluations of the attributes of a Ultisols. In both treatments, Cynodon dactylon received 100 kg of nitrogen during a year. The crops of forage samples were accomplished at every 28 days, making botanical separation and drying the same. After the weighting to calculate the dry matter per area (ha) the samples were crushed for analyses of fiber of neutral detergent (FDN), fiber of acid detergent (FDA), rude protein (PB), calcium (Ca), magnesium (Mg), phosphorus (P) and potassium (K). The samples collecting were taken during January, March, April and October of 2007. The best results of nutritional values were found in the legumes and in the consortium, being with inferior quality the grassy ones. The dry matter present a great variation among the cuts and the forage systems. After the winter the Stylosanthes portions were lost, due to the frosts that happened during this period. This confirms that it not has an adaptation on our conditions of winter. After a year of implantation of the experiment was collected soil to analysis: density of the soil (DS), microporosity (Mip) and macroporosity (Map) porosity and total porosity of the soil (PT) and size of aggregates. In the chemical part, were analyzed total nitrogen (NT), total organic carbon (COT) and phosphorus (P) and potassium (K). DS presented variation between the treatments and the appraised layers, since 1,40 to 1,62 Mg m-3. In Mip and PT didn't present significant differences between the treatments and layers, but Map presented significant differences. In the aggregate size there was significant differences, and the geometric medium diameter (DMG) it varied from 1,41 to 3,21 mm. In the soil chemical attributes both maintained similarities, in other words, larger concentration in the first layer (0 to 5 cm). But some treatments standing out in larger concentration in the first layer, however maintain similarities in the deep layers, unless the potassium (K), that has a distribution more constantly in the evaluated layers.